2012
DOI: 10.1111/j.1469-8137.2012.04368.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide generated by the rice blast fungus Magnaporthe oryzae drives plant infection

Abstract: SummaryPlant-derived nitric oxide (NO) triggers defence, priming the onset of the hypersensitive response and restricting pathogen ingress during incompatibility. However, little is known about the role of pathogen-produced NO during pre-infection development and infection. We sought evidence for NO production by the rice blast fungus during early infection.NO production was measured using fluorescence of DAR-4M and the role of NO assessed using NO scavengers. The synthesis of NO was investigated by targeted k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(118 citation statements)
references
References 96 publications
(132 reference statements)
6
104
0
1
Order By: Relevance
“…The NOS-like proteins described in fungi represent a fungal-specific group of enzymes termed as putative biofunctional p450 reductases, each of which contains an N-terminal cytochrome p450 domain and FAD, NAD, and flavodoxin domains (Samalova et al 2013). In our study, we show that the two NOS-like proteins share a similar domain structure with those described in M. oryzae.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…The NOS-like proteins described in fungi represent a fungal-specific group of enzymes termed as putative biofunctional p450 reductases, each of which contains an N-terminal cytochrome p450 domain and FAD, NAD, and flavodoxin domains (Samalova et al 2013). In our study, we show that the two NOS-like proteins share a similar domain structure with those described in M. oryzae.…”
mentioning
confidence: 70%
“…In higher plants, NO is generated either by NOS or nitrate/nitrite reductase depending on redox status and chemical environment (Gas et al 2009;Fr hlich and Durner 2011). Although some indications for the occurrence of NOS activity in the filamentous fungus Neurospora crassa (Ninnemann and Maier 1996) and I. obliquus Pilat (Zheng et al 2009a) have been demonstrated, the mode for NO biosynthesis remains obscure in fungi (Samalova et al 2013). In this study, we cocultured I. obliquus and Phellinus morii to examine (1) the correlation of inducible production of NO with transcription of genes encoding PAL and 4CL, and (2) the contribution of an inducible NOS-like protein (iNOSL) in NO production in fungal phenylpropanoid metabolism during fungal interspecific interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of the target gene was confirmed by both PCR and Southern blot analysis, as described in Samalova et al (Samalova et al . , 2013). …”
Section: Methodsmentioning
confidence: 99%
“…NO has been shown to be generated in the appressoria of Blumeria graminis and Magnaporthe oryzae to aid penetration of the host (Prats et al, 2008;Samalova et al, 2013). In the case of Phytophthora cryptogea, the virulence factor/elicitor cryptogein aids pathogenesis by promoting host cell death via NO generation (Lamotte et al, 2004).…”
Section: Nitric Oxide In Plant Defencementioning
confidence: 99%